1993
DOI: 10.1002/lsm.1900130411
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of Ga‐Al‐As diode laser irradiation on hyperalgesia in carrageenin‐induced inflammation

Abstract: This study concerned the effect of Ga-Al-As diode laser irradiation (780 nm, continuous wave, 31.8 J/s/cm2, spot size od 0.2 mm, 3 minutes/dose) on hyperalgesia induced in the hind paw of rats by injecting carrageenin. The pressure-pain thresholds of hind paws were measured by the Randall-Selitto test for evaluation of hyperalgesia. Two doses of laser irradiation, given to the inflamed region immediately before and after the injection of carrageenin, partially (approximately 50%) inhibited the occurrence of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
10

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 23 publications
2
35
0
10
Order By: Relevance
“…Currently, there are methods to alleviate the inflammatory process, providing the improvement of cellular nutrition and favoring the injured tissue repair, particularly the low level laser therapy (LLLT) 2,4 . The LLLT has been clinically used for pain control and wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are methods to alleviate the inflammatory process, providing the improvement of cellular nutrition and favoring the injured tissue repair, particularly the low level laser therapy (LLLT) 2,4 . The LLLT has been clinically used for pain control and wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The LLLT has been clinically used for pain control and wound healing. The effectiveness of this therapy is due to responses induced by the cellular level photobiomodulation promoting acceleration of cellular metabolism, reducing inflammation, increasing local microcirculation and the lymphatic system, leading to the decrease of the interstitial edema and increase of the collagen synthesis [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…8 Biological e®ects of light include wound healing, pain reduction, and alleviation of oral mucositis. [9][10][11][12] E®ects such as cytoprotection, cellular proliferation, growth factor release have also been reported. [13][14][15] Studies have indicated the e®ects of NIR on nervous system, like AD.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to attenuation of pain caused by some mechanism unpleasant to the body or by tissue injury, it may be mediated by endogenous opioid system interactions. This is responsible for modulating pain by the action of encephalins and β-endorphins in charge of inducing analgesic effects and influencing nociceptive stimulus perception due to their action on opioid receptors 7 . A possibility for the analgesic effect of low power laser is peripheral opioids release from immune system cells, with significant release of local β-endorphins 8,9 , in addition to the independent effect on opioid receptors 10 .…”
Section: Introductionmentioning
confidence: 99%